Comparative effect of scarification and non-scarification of (Pistacia atlantica) seed in different media and environmental conditions. - Shilan Abdurrahman Mirsar; Payman Hussein Aliehsan Pasha; Hardy Kakakhan Awla Shekhany (Zanco Journal of Pure and Applied Sciences, 2020)
The effect of mechanical scarification on Pistacia atlantica seeds was studied on two different sites (indoor and outdoor) which has different environmental conditions in different media. The study examined 360 seeds (180 scarified and 180 non-scarified), 90 seeds were scarified on each site. Seeds sowed in three different media; Sandy soil, Compost and Peat moss. The statistical analysis applied on seedling parameters showed highly significant variation within-site level and between-site variation. The results of this study showed peat moss had best performance in most of parameters such as stem length 211.17mm, stem diameter 4.23mm, stem wet weight 6.04 mm, stem dry weight 2.59g, root length 484.42mm, root diameter 4.08mm, root wet weight 2.36g and root dry weight 1.08g. Also, interaction effect of scarification, indoor and Peat moss significantly increased all growth parameters.